25th AIAA/CEAS Aeroacoustics Conference 2019
DOI: 10.2514/6.2019-2438
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Slat Noise from the 30P30N at High Angles of Attack using Zonal Hybrid RANS-LES

Abstract: Aeroacoustic predictions of slat noise from the 30P30N three-element high-lift system at high angles of attack are presented using a zonal hybrid RANS-LES method. The simulations are part of the 5 th AIAA Benchmark problems for Airframe Noise Computations (BANC-V) Workshop. An economical approach utilizing structured overset grids with spatially varying span-wise grid resolution and a high-order accurate finite di↵erence method is described. The method is utilized for near-field predictions at three angles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The hybrid RANS-LES model named the stress-blended eddy simulation, or SBES, introduced by Menter [22] is used in this work to provide closure to the Reynolds-averaged Navier-Stokes equations. The use of hybrid RANS-LES models in aerodynamic studies has previously been reported in the literature [23][24][25]. More recently, Syawitri el al.…”
Section: Turbulence Modelingmentioning
confidence: 99%
“…The hybrid RANS-LES model named the stress-blended eddy simulation, or SBES, introduced by Menter [22] is used in this work to provide closure to the Reynolds-averaged Navier-Stokes equations. The use of hybrid RANS-LES models in aerodynamic studies has previously been reported in the literature [23][24][25]. More recently, Syawitri el al.…”
Section: Turbulence Modelingmentioning
confidence: 99%